1,1-Difluoroethyl-substituted triazolothienopyrimidines as inhibitors of a human urea transport protein (UT-B): New analogs and binding model - Liu, Y. (2013)
The kidney urea transport protein UT-B is an attractive target for the development of small-molecule inhibitors with a novel diuretic (‘urearetic’) action. Previously, two compounds in the triazolothienopyrimidine scaffold (1a and 1c) were reported as UT-B inhibitors. Compound 1c incorporates a 1,1-difluoroethyl group, which affords improved microsomal stability when compared to the corresponding ethyl-substituted compound 1a. Here, a small focused library (4a–4f) was developed around lead inhibitor 1c to investigate the requirement of an amidine-linked thiophene in the inhibitor scaffold. Two compounds (4a and 4b) with nanomolar inhibitory potency (IC(50) ≈ 40 nM) were synthesized. Computational docking of lead structure 1c and 4a–4f into a homology model of the UT-B cytoplasmic surface suggested binding with the core heterocycle buried deep into the hydrophobic pore region of the protein.